2013
DOI: 10.1007/s12185-013-1433-6
|View full text |Cite
|
Sign up to set email alerts
|

TIM-3 as a novel therapeutic target for eradicating acute myelogenous leukemia stem cells

Abstract: Acute myelogenous leukemia (AML) originates from self-renewing leukemic stem cells (LSCs), which represent the ultimate therapeutic target for AML. Recent studies have identified several AML LSC-specific surface antigens as candidate targets of therapeutic molecules. T cell immunoglobulin mucin-3 (TIM-3) is expressed on LSCs in most types of AML, with the exception of acute promyelocytic leukemia, but not on normal hematopoietic stem cells (HSCs). In xenograft models reconstituted with human AML LSCs or HSCs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 55 publications
1
40
0
1
Order By: Relevance
“…10 Recent reports also showed that TIM-3, as a surface molecule, is selectively expressed on leukemia stem cells (LSCs) in acute myeloid leukemia (AML), and as such it can be a good target in eradicating AML stem cells, leaving normal hematopietic stem cells intact. [11][12][13] In addition, Tim-3 has also been reported to up-regulate on tumor associated dendritic cells (TADC) and macrophages (TAM), and attenuate the antitumor effects of cancer vaccines 4 ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Recent reports also showed that TIM-3, as a surface molecule, is selectively expressed on leukemia stem cells (LSCs) in acute myeloid leukemia (AML), and as such it can be a good target in eradicating AML stem cells, leaving normal hematopietic stem cells intact. [11][12][13] In addition, Tim-3 has also been reported to up-regulate on tumor associated dendritic cells (TADC) and macrophages (TAM), and attenuate the antitumor effects of cancer vaccines 4 ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Although it is not surprising in mouse models reconstituted with human AML LSCs or human haematopoietic stem cells, a human TIM-3 mouse IgG2a antibody with complementdependent and antibody-dependent cellular cytotoxic activities eradicates AML LSCs in vivo without affecting normal human hematopoiesis. [11][12][13] Thus, TIM-3 may serve as one of the promising targets to eradicate AML LSCs. Jajosky et al also pointed out that, RepSox (a reprogramming tool and inhibitor of transforming growth factor-b receptor 1) accelerated loss of Tim-3 from the surface of AML cells by inhibiting TGF-b signaling.…”
Section: Introductionmentioning
confidence: 99%
“…45,46,53 ATIK2a clone, another mAb that targets human TIM-3, was found to induce antibody-dependent cell-mediated cytotoxicity (ADCC), and was effective in eradicating TIM-3-expressing leukemia stem cells in an acute myeloid leukemia model. 54,55 On the other hand, 334823 and 344801 clones may act as antagonist mAb because the cross-linking of these mAb with its targets on NK cells has suppressed NK cell-mediated cytotoxicity in in vitro experiments. 56 Together, the expression of TIM-3 in innate and adaptive immune cells, in addition to tumor cells, makes it an attractive target to enhance immune responses against tumors or to eradicate TIM-3-expressing cancer stem cells.…”
Section: -16mentioning
confidence: 99%
“…After this finding, the concept of the LSC becomes critical to understand the pathogenesis of leukemia. In this issue, four excellent review articles [1][2][3][4] focus on developmental mechanisms of LSCs to discuss how to eradicate them to obtain absolute cure of leukemia.…”
mentioning
confidence: 99%
“…Ishikawa [3] summarizes the history of xenotransplantation models, and describes his NSG mouse model that is a powerful tool to discover functional properties of LSCs including their cell cycle status and location in the bone marrow. Using the similar xenotransplantation system, Kikushige and Miyamoto [4] describe that targeting TIM-3, an LSC-specific molecule, might be a promising approach to selectively eradicate AML clones. Thus, the xenotransplantation system is useful for preclinical trials to obtain ''proof-ofconcept'' for LSC-targeting therapies.…”
mentioning
confidence: 99%